Consumer Acceptance Analysis of Purchase Interest Using Live Features on The Marketplace with Technology Acceptance Model (TAM) Method Case Study : Shopee - Jhonatan, Edward; Prasetiyo, Budi (Department of Computer Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang, 2023)
The development of technology has become one of the instant lifestyles of the community because it has high mobility in carrying out daily activities. The use of the internet for commercial transactions is known as electronic commerce (e-Commerce). In 2021 Shopee launched a new feature before other competitors had the Shopee live feature. This research is more focused on analyzing buyers using the Shopee live feature on the Shopee marketplace using the Technology Acceptance Model (TAM). The purpose of this study is to analyze how the influence of consumers in buying interest using the Shopee live feature and to determine the effect of each variable used. This type of research is quantitative research. The research sample was 255 UNNES student respondents from 2015-2019. The data analysis method used is descriptive analysis using SEM with SmartPLS 3.0 software. The data that has been obtained is done data cleaning. It was found that the valid data were 203 people. The results of the research based on what has been done on the outer model, there are three indicators that are deleted, namely PEOU 2, PEOU 4, and PU 5, because the results obtained are still below the set value <0.7. In the inner model research, there is one hypothesis that is rejected, namely the t-statistics test, namely PEOU > BI because this hypothesis has a value less than the standard value of the t-test so it is rejected. However, there are six accepted hypotheses, namely PE > PU, PE > PEOU, PE > BI, PT > PU, PT > BI, and PU > BI. Based on the results of this analysis, the six variables have factors that influence the purchase intention using the Shopee live feature.